2019
DOI: 10.3390/s19122736
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Chlorophyll a Fluorescence and Plant Gas Exchange Parameters as Indicators of Drought Tolerance in Perennial Ryegrass

Abstract: Perennial ryegrass (Lolium perenne L.) belongs to the common cultivated grass species in Central and Western Europe. Despite being considered to be susceptible to drought, it is frequently used for forming the turf in urban green areas. In such areas, the water deficit in soil is recognized as one of the most important environmental factors, which can limit plant growth. The basic aim of this work was to explore the mechanisms standing behind the changes in the photosynthetic apparatus performance of two peren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 58 publications
3
82
0
2
Order By: Relevance
“…However, Dąbrowski et al [31] indicated that only F v /F m did not reliably reflect photosynthetic rate in shade-treated Lolium perenne. Recent studies surveyed multiple parameters of prompt and delayed ChlF and observed several parameters highly correlated to photosynthetic rate in Lolium perenne [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, Dąbrowski et al [31] indicated that only F v /F m did not reliably reflect photosynthetic rate in shade-treated Lolium perenne. Recent studies surveyed multiple parameters of prompt and delayed ChlF and observed several parameters highly correlated to photosynthetic rate in Lolium perenne [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that plants used for phytostabilization effectively absorb PTE, and the absorption of Zn, Pb, Cd, and Ni by plant roots generally increases with a rise in pollution levels [29,30]. The applied plants should be characterized by low fertilizer, water, and pesticide requirements, high efficiency of the photosynthetic apparatus, and they should be well adapted to the local climate [44]. Previous research [45,46] and the present findings indicate that PTE impair chlorophyll synthesis and decrease the chlorophyll content of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first works describing the analysis of polyphasic fluorescence rise in photosynthetic material were published and so-called OJIP parameters for this analysis were introduced (Strasser and Strasser 1995, Strasser et al 2000, numerous researchers applied this chlorophyll a fluorecence (ChF) method to examine leaf samples or behaviour of the whole plants under variable growing conditions and under the pressure of any kind of stress. The satisfying informative results were obtained in research detecting stress effects of drought (Živčák et al 2008, Goltsev et al 2012, Wang et al 2012, Oukarroum et al 2018, Dąbrowski et al 2019, heat (Duan et al 2015, Jedmowski andBrüggemann 2015), freezing or chilling (Parvanova et al 2004, Rapacz et al 2015, salinity (Bacarin et al 2011, Dąbrowski et al 2016, Kalaji et al 2018a, contamination with metals and metal oxides and allow to obtain high-time resolution records (with intervals of 10 μs). Such high-time resolution is necessary to visualise so-called prompt (fast) fluorescence rise from the point 0 to the maximal value after the rapid illumination.…”
Section: Introductionmentioning
confidence: 91%